2023
DOI: 10.1007/s12519-023-00701-1
|View full text |Cite
|
Sign up to set email alerts
|

Risk of asthma in preterm infants with bronchopulmonary dysplasia: a systematic review and meta-analysis

Abstract: Background This study aimed to systematically review and meta-analyze the available literature on the association between preterm infant bronchopulmonary dysplasia (BPD) and pre-adulthood asthma. Methods Studies examining the association between BPD and asthma in children and adolescents were systematically reviewed, and a meta-analysis was conducted. We searched Scopus, Embase, Web of Science, PubMed, and Cochrane Library from the database inception to Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Since the 1980s, the incidence of BPD has shown an increase, especially as neonatal monitoring and the survival of extremely preterm infants have improved. BPD in preterm infants may be a major risk factor for the future development of asthma in childhood ( Sun et al, 2023 ). Therefore, the use of early hyperoxia exposure in neonatal mice (BPD model) combined with early ovalbumin (OVA) sensitization can help in understanding the relationship between late childhood BPD and asthma development and formulating effective treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1980s, the incidence of BPD has shown an increase, especially as neonatal monitoring and the survival of extremely preterm infants have improved. BPD in preterm infants may be a major risk factor for the future development of asthma in childhood ( Sun et al, 2023 ). Therefore, the use of early hyperoxia exposure in neonatal mice (BPD model) combined with early ovalbumin (OVA) sensitization can help in understanding the relationship between late childhood BPD and asthma development and formulating effective treatments.…”
Section: Introductionmentioning
confidence: 99%
“…These ndings are consistent with epidemiological data showing increased asthma incidence in children with BPD, and family history of asthma being a risk factor for asthma diagnosis in BPD children. 30 Speci cally, our ndings highlight the signi cance of two intronic SNPs, rs3771150 and rs3771171, within the IL1RL1 and IL18R1 genes. These SNPs, initially identi ed by Floros et al in an African American cohort, were successfully linked to eosinophil percentage in our pediatric cohort, a relationship validated externally.…”
Section: Discussionmentioning
confidence: 62%
“…It is reasonable to say that the overall literature on this topic shows that prematurity is a plausible risk factor for development of asthma and associated poor lung function later in life, but possibly more so in those patients who were born very preterm and complicated by BPD in the first few months-years of life, as highlighted in numerous systematic reviews. [5][6][7][8] In this research article by Kim et al, a decrease in lung function in children with asthma was observed as the birth weight for gestation decreased, and this was noticed in both ex-term and preterm patients on univariate comparison. The authors aimed to assess the independent impact of FGR on lung function but were constrained by the limited number of factors that could be included in the regression analysis.…”
mentioning
confidence: 79%
“…To summarize, the assessment of impact of prematurity on lung function in the current study may be potentially biased by selection of relatively mature preterm babies. It is reasonable to say that the overall literature on this topic shows that prematurity is a plausible risk factor for development of asthma and associated poor lung function later in life, but possibly more so in those patients who were born very preterm and complicated by BPD in the first few months–years of life, as highlighted in numerous systematic reviews 5–8 …”
Section: Figurementioning
confidence: 99%